The Role of Intercultural Communication Competence in Business Collaboration to Develop Start Ups in the Global Era - Siti Nurbaity; John Benedict C. Marasigan; Ravin Kumar A/L Nadarajan (Yayasan Ilomata, 2023)
In this global era, more and more startups are developing their businesses with partners from other regions or countries. However, intercultural cooperation that is not accompanied by intercultural communication competence will often create unresolved conflicts. This research is a qualitative study with a phenomenological approach. In this study, researchers wanted to dig up information about the experiences of informants in developing business partnerships and the difficulties encountered when communicating with business partners from different countries or regions. Data collection was carried out using unstructured interviews so that the informants could be more flexible in sharing their experiences when starting their business development. They can also tell freely about any cultural background conflicts that are often encountered when discussing or communicating with business partners from different cultures. In this study, researchers interviewed 10 informants consisting of start-up actors, who have been in business for more than 5 years and have collaborated with business partners from other regions or countries. This is to dig up information about their experiences when communicating with these business partners and to get data on what obstacles start-ups experience when collaborating with their business partners. The results of this study indicate that Intercultural Communication Competence (ICC), which consists of cognitive, affective and behavioral aspects, is needed by start-ups, especially if they want to develop their business by working with domestic and foreign partners. With the existence of ICC, start-up actors can avoid ethnocentrism, stereotypes and prejudice, as well as language barriers and differences in values.